Resilience and adjustment trajectories amongst children in displacement-affected communities in Zarqa, Jordan - Sabrina Hermosilla; Janna Metzler; Kevin Savage; Alastair Ager (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background The experiences of protracted conflict and displacement are clear threats to children's developmental progress. Understanding the factors that shape the trajectories of children's well-being and adjustment in such contexts is important for informing interventions. # Methods We collected data at three time points from a sample of Syrian refugee and Jordanian children (n=650) residing in Zarqa, Jordan who met eligibility criteria for humanitarian programming. We assessed primary outcomes of protection concerns, caregiver stress, mental health, and developmental assets at three time points: baseline (T1), three months later (T2), and fifteen months after baseline (T3). # Results Over the fifteen-month study period (T1-T3) child protection concerns and mental health symptoms improved, caregiver stress remained constant, and developmental assets deteriorated. School attendance was independently associated with improvements in protection concerns (β = -1.05, *P*=0.01), caregiver stress (β = -0.66, *P* =0.02), and developmental assets (β = 3.84, *P* =0.02). Concern over lost livelihoods significantly predicted higher protection concerns (β = 4.08, *P* <0.001) and caregiver stress (β = 2.32, *P* <0.001). Attending child-focused programming did not significantly impact primary outcomes. # Conclusions This study documents the capacity for adjustment and adaptation of children in the context of protracted displacement. The significant influences of attending school and concern over lost livelihoods on observed trajectories indicate the importance of addressing structural factors, such as education and employment, in supporting processes of resilience in these populations. Programmatic activities for children may secure valuable shorter-term impacts but here, as elsewhere, failed to impact outcomes longer-term.